Going within, between and beyond: An exploration of regular Ashtanga Yoga practitioners’ conceptualizations of five dimensions of wellbeing - Ramirez-Duran, Daniela; Stokes, Helen; Kern, Margaret L. (Frontiers in Psychology, 2022)
Yoga is an embodied practice underpinned by philosophical elements, seeking to evolve different dimensions of human existence for optimal functioning in relation to oneself, others and beyond. This mixed-methods research focused on 137 regular Ashtanga Yoga practitioners (AYPs) by investigating their conceptualizations of five dimensions of wellbeing (i.e., physical, emotional, psychological, social, spiritual). Conceptualizations were analysed through word count analysis and Reflexive Thematic Analysis separately for each dimension, yielding four themes in each case, which partly aligned with existing wellbeing and yoga models, and partly extended on the existing literature. Further higher level analysis identified shared meanings across these five dimensions, expressed in themes grouped within five topics (i.e., freedom from and managing suffering, a positive and integrated sense of self, a sense of equanimity and steadiness, the self in relation to others and the world, meta-awareness). Furthermore, it also portrayed each dimension as multileveled, represented in three levels of human functioning. The foundational level encompassed the absence and managing suffering, representing functioning in coping and recovery mode. The optimal functioning level included a positive and integrated sense of self, a sense of equanimity and steadiness, and the self in relation to others and the world, representing functioning in personal development and growth mode. The contemplative and transcendental level involved meta-awareness in every dimension of wellbeing, representing functioning in transpersonal mode. As a result, we propose a preliminary model informed both by this empirical work and previous theories. While the continuousness of themes across dimensions reinforces the importance of embodiment and transcendence in wellbeing frameworks, the notion of the self as a multi-level system could be further explored in relation to knowing about and cultivating wellbeing.